2021
DOI: 10.3389/fgene.2021.698477
|View full text |Cite
|
Sign up to set email alerts
|

ACP-DA: Improving the Prediction of Anticancer Peptides Using Data Augmentation

Abstract: Anticancer peptides (ACPs) have provided a promising perspective for cancer treatment, and the prediction of ACPs is very important for the discovery of new cancer treatment drugs. It is time consuming and expensive to use experimental methods to identify ACPs, so computational methods for ACP identification are urgently needed. There have been many effective computational methods, especially machine learning-based methods, proposed for such predictions. Most of the current machine learning methods try to find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 51 publications
0
30
0
Order By: Relevance
“…To ensure the effectiveness and efficiency of the proposed method, we compared the performance of ACP-ADA with ACP-DA [ 19 ], ACP-DL [ 17 ], AntiCP2.0 [ 18 ], and DeepACP [ 15 ] while relying on the same main and benchmark datasets and corresponding classification evaluation metrics.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To ensure the effectiveness and efficiency of the proposed method, we compared the performance of ACP-ADA with ACP-DA [ 19 ], ACP-DL [ 17 ], AntiCP2.0 [ 18 ], and DeepACP [ 15 ] while relying on the same main and benchmark datasets and corresponding classification evaluation metrics.…”
Section: Resultsmentioning
confidence: 99%
“…AntiCP 2.0, an updated model for the prediction of ACPs using various features and different classes of machine learning classifiers on two datasets-ACP740 and ACP240, has been proposed for the prediction of ACPs [ 18 ]. A data augmentation method named ACP-DA, which uses sequential features and a multi-layer perceptron (MLP) classifier to predict ACPs using sequential physiocochemical features, has been proposed as well [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Especially, in DeepACP, CNN, RNN, and CNN-RNN models were compared, and RNN showed the best performance [ 63 ]. Additionally, hybrid learning is used for ACP development in ACP-DA [ 65 ] and by Lv et al [ 25 ]. AI tools for ACP prediction are summarized in Table 2 .…”
Section: Development Of Therapeutic Acpsmentioning
confidence: 99%
“…In Lv et al’s hybrid learning process, data split, embedding, and feature extraction are performed by the DL method, and classification is performed by the ML method [ 25 ]. On the other hand, in ACP-DA, data split and feature extraction are performed by the ML method, and classification is performed by the DL method [ 65 ]. After classification in AI methods, prediction is performed [ 144 ].…”
Section: Application Of ML and Dl For Acp Developmentmentioning
confidence: 99%
“…In 2019,Yi Haichent et al proposed a deep learning long short-term memory (LSTM) neural network model, called ACP-DL [ 10 ], which developed an efficient feature representation approach by integrating binary profile features, k-mer sparse matrix of the reduced amino acid alphabet and then implemented a deep LSTM model to identify ACPs. In 2021, Chen Xiangan et al proposed an ACP prediction model, called ACP-DA [ 11 ], which uses data augmentation for insufficient samples and trains a multilayer perception model to improve the prediction performance. In 2020, Yu Lezheng et al found that the recurrent neural network with bidirectional long short-term memory cells is a superior architecture to identify ACPs and implement a sequence-based deep learning tool, called DeepACP [ 12 ], to accurately predict ACPs.…”
Section: Introductionmentioning
confidence: 99%